Uniqueness solution of the finite elements scheme for symmetric hyperbolic systems with variable coefficients - Aloev R.D.; Davlatov S.O.; Eshkuvatov Z.K.; Nik Long N.M.A. (Universiti Putra Malaysia, 2024)
Indexed by WOS/ Scopus